2001
DOI: 10.1007/s003300101047
|View full text |Cite
|
Sign up to set email alerts
|

Atypical evolution of a calcified lipid cyst presenting spontaneously as a suspicious cluster of microcalcifications

Abstract: We report an infrequent mammographic case in which a gross-calcified lipid cyst evolved spontaneously to form a cluster of pleomorphic microcalcifications which were indistinguishable from those seen in breast cancer. The biopsy performed was consistent with fat necrosis. Ultrasonography of the specimen showed a nodule with mixed echogenicity surrounded by a hypoechoic rim. To our knowledge, this behavior is extremely rare, with only one similar case reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Mammographic follow‐up studies for periods of more than 3 years revealed a variety of patterns in the evolution of fat necrosis: radiolucent oil cysts and calcifications developed in areas of round opacity; dystrophic calcifications coarsened; nodular opacity with dystrophic calcifications disappeared; a suspicious spiculated mass formed a radiolucent oil cyst; gross calcified lipid cyst transformed spontaneously into a cluster of suspicious microcalcifications (10,11). Awareness of the broad spectrum of fat necrosis ranging from oil cysts to lipophagic granulomas, and close follow‐up with imaging and physical examination may reduce the number of unnecessary biopsies (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…Mammographic follow‐up studies for periods of more than 3 years revealed a variety of patterns in the evolution of fat necrosis: radiolucent oil cysts and calcifications developed in areas of round opacity; dystrophic calcifications coarsened; nodular opacity with dystrophic calcifications disappeared; a suspicious spiculated mass formed a radiolucent oil cyst; gross calcified lipid cyst transformed spontaneously into a cluster of suspicious microcalcifications (10,11). Awareness of the broad spectrum of fat necrosis ranging from oil cysts to lipophagic granulomas, and close follow‐up with imaging and physical examination may reduce the number of unnecessary biopsies (10,12).…”
Section: Discussionmentioning
confidence: 99%